In vitro synthesis of beta-galactosidase with ilv-lac fusion deoxyribonucleic acid as template. - Wild, J (1977)
An in vitro protein-synthesizing system has been developed to study the mechanism of induction of ilvC gene in Escherichia coli strain K-12. Deoxyribonucleic acid (DNA) from a lambda phage carrying an ilvC-lac fusion was employed as a template for the in vitro synthesis of beta-galactosidase under the control of the ilvC promoter. The use of this template allowed an investigation of the components required for induction of the ilvC gene and the kinetics of the induction. The in vitro synthesis of beta-galactosidase under the control of the ilvC promoter was found to be DNA, acetohydroxy acid, and guanosine-3'-diphosphate-5'-diphosphate dependent, and sensitive to rifampin, actinomycin D, and chloramphenicol. Uncoupling experiments indicate that the inducer, acetohydroxybutyrate, acts at the transcriptional level. Investigation of a proposed noninducible ilvC regulatory mutant has shown normal induction in vitro. It was also observed that an intact ilvA gene is not required for the induction of the ilvC gene.